Fluoxetine for the Symptomatic Treatment of Multiple System Atrophy: The MSA‐FLUO Trial. Issue 7 (1st April 2021) - Rascol, Olivier; Cochen de Cock, Valérie; Pavy‐Le Traon, Anne; Foubert‐Samier, Alexandra; Thalamas, Claire; Sommet, Agnes; Rousseau, Vanessa; Perez‐Lloret, Santiago; Fabbri, Margherita; Azulay, Jean Philippe; Corvol, Jean‐Christophe; Couratier, Philippe; et al.
ABSTRACT: Background: There are no effective treatments for multiple system atrophy (MSA). Objective: The objective of this study was to assess the efficacy and safety of the serotonin reuptake inhibitor fluoxetine (40 mg/d) for the symptomatic treatment of MSA. Methods: This was a double‐blind, parallel‐group, placebo‐controlled, randomized trial in patients with "probable" MSA. The primary outcome was the change from baseline to week 12 in the mean total score of the Unified MSA Rating Scale (UMSARS Parts I + II). Secondary outcomes included change from baseline to week 6 in total UMSARS, and change from baseline to week 12 in the Scales for Outcomes in Parkinson Disease–Autonomic Dysfunction, Beck Depression Inventory, and different domains of the MSA‐Quality of Life Questionnaire. Exploratory outcomes included change from baseline to week 12 in the UMSARS Parts I and II separately and change from baseline to week 24 in the total UMSARS score. Results: A total of 81 patients were randomly assigned, with no significant difference in the primary outcome (−2.13 units [95% confidence interval, CI, −4.55 to 0.29]; P  = 0.08). There was a greater reduction on fluoxetine in the change from baseline to 12‐week in UMSARS Part II (exploratory outcome: −1.41 units [95% CI, −2.84; 0.03]; p = 0.05) and in MSA‐QoL emotional/social dimension (secondary outcome: −6.99 units [95% CI, −13.40; −0.56]; p < 0.03). A total of 5 deaths occurred (3 on fluoxetine and 2 on placebo). Conclusion: The MSA‐FLUO failed to demonstrate fluoxetine superiority over placebo on the total UMSARS score, whereas trends in motor and emotional secondary/exploratory outcomes deserve further investigation. © 2021 International Parkinson and Movement Disorder Society